2020
DOI: 10.24925/turjaf.v8i5.1160-1165.3335
|View full text |Cite
|
Sign up to set email alerts
|

Farklı Zamanlarda Ekilen Maş Fasulyesinin (Vigna radiata (L.) Wilczek) Bazı Tarımsal Özellikleri ve Ot Kalitesi Üzerine Bir Araştırma

Abstract: This study was carried out in the research field of Department of Field Crops, Faculty of Agriculture, Kahramanmaraş Sütçü İmam University. The research was conducted to determine the optimum planting time of mung bean (Vigna radiata (L.) Wilczek) in Kahramanmaraş ecological conditions. The experiment was established as a randomized block design with three replications. Mung bean seeds were sown at five different sowing times (30 March, 15 April, 30 April, 15 May and 30 May). According to the results of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The highest number of pods as an average of potassium doses was obtained from the Turkmenistan genotype with 53.28 units/plant, and the average of genotypes was obtained from a potassium dose of 20 kg/da with 49.71 units/plant (Table 2). When the researchers' studies on the number of pods are examined; Gebeloğlu and Yazgan (1992) 11.93-35.20 units/plant, Gul et al (2007) 32.66-58.66 units, Akgündüz (2016) 31.51-33.29 units, Karaman (2019 18.70-42.06 units in its first year, 36.88-48.62 units in its second year, Akbay et al (2020) reported that it varies between 9.43-23.98 units/plant. The reason for the differences between the findings is thought to be the result of the differences in the number of pods caused by different ecologies and cultivars/genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest number of pods as an average of potassium doses was obtained from the Turkmenistan genotype with 53.28 units/plant, and the average of genotypes was obtained from a potassium dose of 20 kg/da with 49.71 units/plant (Table 2). When the researchers' studies on the number of pods are examined; Gebeloğlu and Yazgan (1992) 11.93-35.20 units/plant, Gul et al (2007) 32.66-58.66 units, Akgündüz (2016) 31.51-33.29 units, Karaman (2019 18.70-42.06 units in its first year, 36.88-48.62 units in its second year, Akbay et al (2020) reported that it varies between 9.43-23.98 units/plant. The reason for the differences between the findings is thought to be the result of the differences in the number of pods caused by different ecologies and cultivars/genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…As it can be understood from here, it is thought that the genetic structure causes the high number of leaves in the Turkmenistan genotype even though the same potassium dose is applied. When the researchers' studies on the number of leaves are examined; Toker et al (2002) 12-25 units/plant, Dalkılıç (2010) 21.99 units/plant, Baydemir (2013) 17.49 units/plant, Akbay et al (2020) reported that it varies between 47.30-73.77 units/plant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation